1992
DOI: 10.2135/cropsci1992.0011183x003200040035x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Phosphorus Availability and Pearl Millet Water‐Use Efficiency

Abstract: Pearl millet [Pennisetum glaucum (L.) R. Br.] production in the West African Sahel is constrained by low, erratic rainfall and low soil nutrient (particularly P) availability. Outdoor pot and growth chamber experiments tested the hypothesis that increasing soil P supply increases transpirational water‐use efficiency (WUET), under waterstressed and non‐water‐stressed conditions. Pearl millet was grown outdoors under semiarid conditions in covered pots containing 85 kg of acid, P‐deficient Betis sand (sandy, sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 0 publications
5
44
0
Order By: Relevance
“…To survive under drought condition, the nutrient status of plants plays a significant role in increasing plant tolerance to drought stress (Table 1) (Payne et al, 1992;Marschner, 1995;Rizhsky et al, 2004;Samarah et al, 2004;Yasar et al, 2006;Rotaru and Sinclair, 2009;Rotaru, 2011;Waraich et al, 2011). A study showed that sunflower develops drought resistance with the help of application of micronutrients (Rahimizadeh et al, 2007).…”
Section: Iron and Drought Stressmentioning
confidence: 99%
“…To survive under drought condition, the nutrient status of plants plays a significant role in increasing plant tolerance to drought stress (Table 1) (Payne et al, 1992;Marschner, 1995;Rizhsky et al, 2004;Samarah et al, 2004;Yasar et al, 2006;Rotaru and Sinclair, 2009;Rotaru, 2011;Waraich et al, 2011). A study showed that sunflower develops drought resistance with the help of application of micronutrients (Rahimizadeh et al, 2007).…”
Section: Iron and Drought Stressmentioning
confidence: 99%
“…Unfortunately, it is difficult to measure water extraction precisely in the field, especially the small but key amounts that may be extracted during the grain filling period; however, a lysimetric method now exists in which a precise water extraction measurement is possible at all crop stages (e.g. Payne et al 1992;Vadez et al 2008). This method indeed confirms that the extraction of small amounts of water at key stages is critical and likely more informative than measuring total water extraction (Ratnakumar et al 2009;Zaman-Allah et al 2011a;Vadez et al 2013b).…”
Section: The Need For Dynamic Measurements Of Water Extraction At Keymentioning
confidence: 99%
“…Despite numerous reports about the effects of P deficiency and water stress on millet growth (Manu et al 1991;Buerkert 1995;Bagayoko et al 2000;Brück et al 2003;Valluru et al 2009;Vadez et al 2013), to our knowledge studies investigating the combination of both major stress factors on plant development are lacking, except few (Payne et al 1990(Payne et al , 1992. The novelty of the present study is then in addressing this knowledge gap by using a lysimeter system consisting of large PVC tubes in which plants can be grown in a soil volume allowing soil exploration by the plant similar to field conditions, and where the effects of a factorial of P and water treatments can be investigated.…”
Section: Introductionmentioning
confidence: 99%